Whisper not the autobiography of Benny Golson - Golson, Benny 1929-2024 (Temple University Press, 2016)
Born during the de facto inaugural era of jazz, saxophonist Benny Golson learned his instrument and the vocabulary of jazz alongside John Coltrane while Golson was still in high school in Philadelphia. Quickly establishing himself as an iconic fixture on the jazz landscape, Golson performed with dozens of jazz greats, from Sonny Rollins, Coleman Hawkins, and Jimmy Heath to Dizzy Gillespie, Freddie Hubbard, and many others. An acclaimed composer, Golson also wrote music for Hollywood films and television and composed such memorable jazz standards as "Stablemates," "Killer Joe," and "Whisper Not." An eloquent account of Golson's exceptional life-presented episodically rather than chronologically-Whisper Not includes a dazzling collection of anecdotes, memories, experiences, and photographs that recount the successes, the inevitable failures, and the rewards of a life eternally dedicated to jazz. - Benny Golson is an NEA Jazz Master, composer, arranger, and saxophonist. After helping Art Blakey revamp his regime with the Jazz Messengers, he co-founded Jazztet with trumpeter Art Farmer. He has composed not only jazz standards, including "Killer Joe" and "Along Came Betty," but also music for films and television, including It Takes a Thief and M*A*S*H. Jim Merod has recorded a veritable "who's who" of jazz greats under his BluePort Jazz label. He is a Professor of Literature and Humanities at Soka University, who has also taught at Cornell, Brown, Brandeis, Stanford, and UCLA. He is the author of The Political Responsibility of the Critic and the editor of Jazz as a Cultural Archive, a special issue of the journal boundary 2.
Keywords: Golson, Benny; Golson, Benny -- 1929-2024; Geschichte 1929-; Jazz musicians -- United States -- Biography; Saxophonists -- United States -- Biography; Saxofonist; Komponist; Jazzmusiker; USA; Autobiografie; Biografie